Pengembangan Kewirausahaan Di Universitas Mulawarman Untuk Mencetak Wirausaha Muda Yang Inovatif - Jawatir Pardosi; Julinda Romauli Manullang; Rudy Agung Nugroho; Andi Noor Asikin (Jurnal Pengabdian UntukMu NegeRI, 2020)
The percentage of entrepreneurs is very small, it needs concrete efforts to grow and develop the entrepreneurial spirit in higher education which is expected to encourage students to be enthusiastic about entrepreneurship. The purpose of the Entrepreneurship Development Program (PPK) activity is to develop entrepreneurship at Mulawarman Universit. Socialization to students and until the end of the registration as many as 49 students / alumni registered. Implementation of entrepreneurship training activities via offline and online, training materials covering theory and practice as well as conducting field visits to advanced MSME entrepreneurs. Business proposal presentations were also conducted to determine the tenants who passed the selection. Business apprenticeship at an apprenticeship place that is in accordance with tenant business products, guidance and consultation are carried out periodically as well as assistance in the preparation of business proposals to be marketed through social media and E Commerce. The KDP website was created contained information on KDP activities and tenant products. Periodic guidance and consultation are also carried out through off line and on line as well as assistance in the preparation of scientific-based business proposals and product improvements to be marketed through social media and E Commerce